Fluticasone/formoterol dry powder versus budesonide/formoterol in adults and adolescents with uncontrolled or partly controlled asthma - Cukier, A.; Jacob, C. M. A. [UNESP]; Rosario Filho, N. A.; Fiterman, J.; Vianna, E. O.; Hetzel, J. L.; Neis, M. A.; Fiss, E.; Castro, F. F. M.; Fernandes, A. L. G.; Stirbulov, R.; Pizzichini, E. (W B Saunders Co Ltd, 2013)
This 12-week study compared the efficacy and safety of a fixed combination of fluticasone propionate plus formoterol (FL/F) 250/12 mu g b.i.d. administered via a dry powder inhaler (DPI) (Libbs Farmaceutica, Brazil) to a combination of budesonide plus formoterol (BD/F) 400/12 mu g b.i.d. After a 2-week run-in period (in which all patients were treated exclusively with budesonide plus formoterol), patients aged 12-65 years of age (N = 196) with uncontrolled asthma were randomized into an actively-controlled, open-labeled, parallel-group, multicentre, phase III study. The primary objective was to demonstrate non-inferiority, measured by morning peak expiratory flow (mPEF).The non-inferiority was demonstrated. A statistically significant improvement from baseline was observed in both groups in terms of lung function, asthma control, and the use of rescue medication. FL/F demonstrated a statistical superiority to BD/F in terms of lung function (FEV1) (p = 0.01) and for asthma control (p = 0.02). Non-significant between-group differences were observed with regards to exacerbation rates and adverse events.In uncontrolled or partly controlled asthma patients, the use of a combination of fluticasone propionate plus formoterol via DPI for 12-weeks was non-inferior and showed improvements in FEV1 and asthma control when compared to a combination of budesonide plus formoterol. (Clinical Trial number: ISRCTN60408425). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Asthma control questionnaire; Clinical trial; Forced expiratory volume in 1 s; Single inhaler; Non-inferiority; Morning peak expiratory flow